Central nervous system involvement in ANCA-associated vasculitis - Öğüt, Tahir Saygın; Yazısız, Veli (Acta Medica, 2025)
Anti-neutrophil cytoplasmic antibody (ANCA)–associated vasculitides (AAV) are rare but heterogeneous disorders. Although central nervous system (CNS) involvement is relatively uncommon, it is associated with substantial morbidity. Neurological involvement in AAV spans a broad spectrum. Diagnosis relies on clinical findings together with imaging—magnetic resonance imaging (MRI) being the mainstay—with dural thickening and characteristic signal changes serving as distinguishing features. When indicated, cerebrospinal fluid (CSF) analysis and tissue biopsy increase diagnostic certainty. On clinicoradiologic grounds, two principal phenotypes can be recognized: a granulomatous phenotype (pachymeningitis, intracranial granuloma, hypophysitis) and a vasculitic phenotype (ischemic/hemorrhagic stroke). These phenotypes may differ in immunologic underpinnings, clinical manifestations, therapeutic response, and prognosis. Induction therapy typically consists of high-dose corticosteroids combined with cyclophosphamide or rituximab, followed by long-term maintenance immunosuppression. Recognizing relationships between clinicoradiologic CNS subtypes and accompanying clusters of extra-CNS organ involvement may provide important clues for diagnostic evaluation and management.